La presenza/assenza dello psichiatra nella psicoterapia online - Fargnoli, Francesco (Il sogno della farfalla, 2021)
As a result of Covid-19 pandemic and the consequent lockdown, many psychiatrists and psychotherapists have questioned if and how to carry on the psychotherapeutic practice. Firstly, it was considered to suspend the sessions until the end of the lockdown restriction. A question was raised about whether it was fundamental to respond exclusively to emergencies or if it was necessary to find alternative solutions in order to ensure the continuity of therapeutic relationships. The cessation of psychotherapy drew the attention to the absence of the analyst. The suspension usually occurs during the summer break, as previously arranged between the doctor and the patient. In this case, external events determined the impossibility to carry on the psychotherapeutic sessions. These caused a forced interruption without knowing its potential duration, although it could be easily hypothesized that this period would have lasted long. The author discusses whether it was appropriate to start the use of telemedicine in order to continue the sessions and at the same time questions how relevant changes in the setting would represent a risk or even a threat to the efficacy of the psychotherapeutic practice.